Gamification as an Educational Strategy to Increase Motivation and Academic Performance - Díaz Estrada, Diana Margarita; Díaz Zúñiga, Edgar Juan; Pilco Lozano, María Adelaida (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This article presents the design and implementation of an educational strategy based on gamification, whose objective was to motivate students and encourage active participation in virtual classes. The experience was developed with 35 undergraduate students from the National University of Ucayali in the subject Systems Design. Where a diagnosis of the needs and interests of the students was carried out, the technological tools were selected to design and implement Gamification scenarios and finally the results showed a good level of acceptance of the strategy that favored learning and improved the pass rate with compared to previous years.